PENGARUH JENIS FESES TERNAK BERBEDA SEBAGAI MEDIA KULTUR TERHADAP PERTAMBAHAN POPULASI CACING TANAH (Lumbricus rubellus) - Muhammad Hasby (DINAMIKA PERTANIAN, 2018)
This research aims to determine the test of the effect of different types of feces of livestock as a culture media on the increase in earthworm populations (L. rubellus). The research was conducted for 42 days starting on October 19 - November 30, 2017, at the Fish Seed Center (BBI) Faculty of Agriculture, Riau Islamic University, Pekanbaru. The method used in this study was an experimental method using a Completely Randomized Design (CRD) with five treatments and three replications. The treatments used as experiments in this study were: P0: using 100% soil, P1: using 100% buffalo feces, P2: using 100% goat manure, P3: using 100% cow dung, P4: using 25% soil + buffalo feces 25 % + goat feces 25% + cow feces 25%. Treatment experiments were carried out on earthworms (L. rubellus). The container used is 15 units of the tray (tray) with a size of 30 x 40 cm that has been filled with fecal treatment media and soil as high as 10 cm with 160 individual stocking densities. As a result, it was known that the highest increase in earthworm population is found in the treatment of P1 using 100% buffalo feces with a population increase of 7926 individuals and the lowest was in the P0 treatment using 100% of the soil where there was no increase in earthworm population (L rubellus). Analysis of variance showed that Fcount 68,01> Ftable (0,01) 9,77 were at the accuracy level of 99%, where the administration of different types of feces to the increase in earthworm populations (L. rubellus) had significantly different. Climatic data in the form of average temperature measurement ranged from 24-280C, Humidity 4-10 (moisture meter) and pH of media during the study ranged from 6,4-7.